유비쿼터스 컴퓨팅 환경에서 상황정보를 수집하기 위한 컨텍스트 분류 - 박유상(Yoosang Park); 조용성(Yongseong Cho); 최종선(Jongsun Choi); 최재영(Jaeyoung Choi) (정보과학회 컴퓨팅의 실제 논문지, 2016)
상황인지 시스템은 주변상황을 인지하고 사용자에게 적합한 서비스를 제공하기 위해서 센서데이터 수집 모델과 컨텍스트 표현모델이 필요하다. 센서데이터 수집 모델은 센서접근정보, 센서 값과 타입정의로 구성된다. 컨텍스트 표현모델은 마크업 언어로 기술되며, 센서데이터 수집 모델이 제공하는 정보와주변상황을 정의하기 위한 키워드로 구성된다. 그러나 서비스 개발자가 컨텍스트 정보를 기술할 때, 하나의 주변상황에 대한 키워드를 중복하여 사용하면 센서 식별을 위한 접근정보가 불분명해진다. 이러한 이유로 상황인지 시스템은 컨텍스트 정보를 올바르게 판단할 수 없다. 본 논문에서는 상황에 적합한 올바른컨텍스트 정보를 얻기 위해, 센서 정보를 식별하기 위한 컨텍스트 분류 모델을 제안한다. 그리고 실험을통해 컨텍스트 정의가 갖는 효용성을 보인다. Context-aware systems require sensor data collecting model and context representing model to provide user-demand services. Sensor data collecting model consists of sensor access information, sensor value, and definition of value types. Context representing model involves certain keywords to symbolize environmental information including the field from sensor data collecting model that is described in markup language such as XML. However, duplicated keywords could be assigned to different contextual information by service developers. As a result, the system may cause misunderstanding and misleading wrong situational information from unintended contextual information. In this paper, we propose a context classification model for collecting appropriate access information and defining the specification of context. KCI Citation Count: 0